"They say we have a choice, but we don't": A gendered reflection on work-family strategies and planning systems of atypical schedules within male-dominated occupations in Canada and Switzerland. (February 2020) - Lefrançois, Mélanie; Probst, Isabelle
Abstract: For parents working in the transportation industry, atypical schedules are often a daily puzzle. Schedule planning systems allowing workers to choose shifts may affect job strenuousness and work-family balance (WFB) for both female and male workers. How could ergonomic interventions related to the implementation of those systems better consider gender dynamics regarding WFB strategies, and minimize inequities among workers? This article presents a joint analysis of two independent case studies related to ergonomic interventions in transport companies in Canada and Switzerland. Direct observation and semi-structured interviews shed light on the characteristics of schedule planning systems and their interaction with men's and women's WFB strategies. Issues related to each step of the planning process (shift construction, schedule choice, day-to-day schedule management) are discussed to inform interventions aimed at facilitating WFB, and ultimately gender equity, in atypical schedule contexts. Highlights: Schedule length, shift sequence type, and shift trades impact WFB strategies. Individual flexibility favors senior workers more than junior workers and caregivers. Fathers in caregiving roles faced challenges similar to women. Schedule choices are not individual but collective issues. Gender-equitable scheduling systems grasp the complexity of workers' WFB strategies.